PENGARUH KEDALAMAN TERHADAP PERTUMBUHAN RUMPUT LAUT Kappaphycus alvarezii MENGGUNAKAN METODE LONGLINE - Andiska Andis; Henky Irawan; Rika Wulandari (Intek Akuakultur, 2021)
The aim of the research was to evaluate the influence of depth on the growth of seaweed K. alvarezii. This research was conducted on 21 November 2020 – 04 January 2021 for 45 days with 3 days acclimatization in Berakit Village, Bintan Regency, Riau Islands Province. The method used is experimental with a complete randomized design (RAL) with 3 treatments and 3 repeats. Analysis of ANOVA data using JASP application shows that depth of 25cm or A treatment is the best result compared to other treatments. Results obtained at the specific growth rate of K. alvarezii seaweed amounted to (6.74 ± 0.01 % / day), the absolute weight of K. alvarezii seaweed amounted to (283.24 ± 0.44 g). and the absolute growth of K. alvarezii seaweed by (183.24 ± 0.44 g). The results showed that treatment A is the best treatment for growth